Implementasi Algoritma Greedy dan Algoritma A* Untuk Penentuan Cost Pada Routing Jaringan - Ristasari Dwi Septiana; Dimas Abisono Punkastyo; Nurhasan Nugroho (STMIK Budi Darma, 2022)
The current increase in internet development raises new problems in terms of path optimization on the internet. This makes network path optimization a major problem in choosing the shortest route. The purpose of this research is to understand and compare the process of finding the shortest route using two algorithms, namely Greedy and A*. The A* algorithm has an advantage in overcoming network workloads compared to the Greedy algorithm. In implementation, both algorithms have the same results in determining the delivery path. However, the A* algorithm is more effective for use on large and complex networks because it has more certain and accurate calculations. From the test results, it was found that the A* algorithm has better performance than the greedy algorithm in the test. Where the final cost value of the greedy algorithm is 49, while for the A* algorithm is 48